PENGARUH PENERAPAN TEKNIK KANCING GEMERINCING DALAM PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS X SMK KESEHATAN PRO-SKILL INDONESIA - Rahayu, Elsya; Murni, Atma; ', Sakur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The background of this study is students low mathematice achievement of X grade at SMK Kesehatan pro-skill Indonesia. This research conducted in second semester of academic years 2016/2017. The aimed of study is to find out whether there is significant effect of using “Kancing Gemerincing” as a technique in cooperative learning (STAD) toward mathematice achievements of students grade X at SMK Kesehatan pro-skill Indonesia. The study employed the pre-experimental research focus on post-test in control group design. The sampling of technique was purposive. There were two sampling in this study; the experimental class was using “kancing gemerincing” as a technique and the control class with conventional learning. The instruments in this research are the results of students test and the observation sheet of teacher and students activities. The finding of this research showed experimental class better than control class. So, it can be concluded there was effect of using “kancing gemerincing” as a technique in cooperative learning (STAD) toward mathematice achievements of students grade X at SMK Kesehatan pro-skill Indonesia.Key Word : The result of mathematical, “Kancing Gemerincing” as a technique,cooperative learning (STAD), pre-experimental research.